Evaluation of antibacterial efficacy of propolis as an intercanal medicament against Enterococcus faecalis (a randomized controlled in vitro study) - Alaa Almahameed; Joul Kassis; Magd Aboud; Kinda Layous (Heliyon)
Background: Enterococcus faecalis (E. faecalis) is one of the microorganisms responsible for the pathology of root canals. We aimed in this study to determine the efficacy of two different pastes (calcium hydroxide combined with saline and calcium hydroxide combined with propolis) as a dressing material in eradicating E. faecalis from infected root canals. Methods: Twenty extracted single-rooted and single-canalled first premolars randomly distributed into two equal groups of 10 teeth each. Each canal was first injected with the prepared bacterial suspension, which was cultured with E. faecalis aerobically in the incubator at 37 °C for 7 days. Then they were irrigated with NaOCl, and finally, groups 1 and 2 were stuffed with (calcium hydroxide + saline) and (calcium hydroxide + propolis) pastes, respectively. Both groups were cultured for 7 days in a moist environment. Bacterial colonies' units were counted at three different times (T0; after bacterial injection, T1; after NaOCl irrigation, and T2; after paste application). Data were analyzed using a T-test (P-value≤0.05) as the significance level. Results: The mean value of the E. faecalis count at the time T2 was 0.030 for group 2, which is less and better than in group 1 (0.363). Statistical analysis showed that the difference in the E. faecalis count at T2 between the studied groups was 2.192 and a P-value of 0.042, indicating that there is a statistically significant difference between the two studied groups. Conclusion: Propolis-containing paste had a remarkable ability to reduce the bacterial enumeration of E. faecalis in root canals.